Some problems of prevention of substitution of the child in the Republic of Kazakhstan (Journal of actual problems of jurisprudence, 2019)
This article examines the following issues as a criminological aspects of the substitution of the child, the legal characteristics of public risk and ways of preventing criminal pravonarushenii against minors. The main purpose of the article is to implement legal measures to ensure that every child grows up and stays in the family, together with his or her own parents, and to avoid the wrongful act as a substitute for the child.The scientific significance of this article suggests that this study has not been studied previously in Kazakhstan and the CIS (Commonwealth of Independent States).This scientific article is aimed at the study of criminological characteristics and prevention of crime under article 136 «Substitution of the child» of the Criminal Code of the Republic of Kazakhstan. The study used comparative legal, historical and logical, statistical, expert-evaluation methods. The value ofthe study is that it has not been previously considered by other Kazakh authors. The results of the workcan be applied in law enforcement practice. This article discusses the concept of substitution of the child,the problem of prevention and prevention of substitution of the child, some information about the factsof substitution of the child, the responsibility of health workers, etc.Key words: child, parents, family, minors, crime, trafficking, DNA.